The Utilisation Of Thermal Methods For The Screening Of Three Component Co-amorphous Systems - Alessandra D'Angelo; Benjamin Edgar; Milan Antonijevic (University of Huddersfield Press, 2018)
Indomethacin and piroxicam are known to become amorphous upon rapid cooling after melting. Multiple three-component co-amorphous mixtures have been produced via a melt quench method to evaluate the influence of the third component on stability and physical properties on the co-amorphous mixture of piroxicam and indomethacin. These have then been tested using thermal gravimetric analysis, differential scan calorimetry and hot stage microscopy. Results have confirmed the creation of a three-component co-amorphous system.